Learning Effectiveness of Social Work Methods With Groups, in Online and Face-to-Face Contexts - Neamţu, Nicoleta; Faludi, Cristina (Frontiers in Psychology, 2021)
During the last three decades, thousands of highly qualified social workers who graduated from Romanian universities were employed in the public systems of social work of the European Union. Social group work is studied as a compulsory discipline for the undergraduate students. The major focus of our study is on the effectiveness of students' learning of Social Work Methods with Groups (SWMG), using workshops in an undergraduate full-time program from Romania. We were interested to find out what are the students’ perceptions about their learning processes and outcomes, in the context of teaching the same discipline exclusively in the online medium, due to the pandemic, and in the face-to-face environment via traditional classroom instruction. This study has a mainly quantitative design, covering two academic years between 2018 and 2020, for the two cohorts of social work students. The core analysis is focused on the activities of students at the SWMG laboratories: 50 students in 2020 and 92 students in 2019. Descriptive, inferential statistics and thematic content analysis were applied on two types of students’ deliverables: the self-assessment sheet and the group plan. The results of our study showed that training of cognitive and self-awareness skills prevailed among the students who learned online in 2020, while the acquisition of interpersonal skills was reported at a significantly higher level by students who learned in the face-to-face medium in 2019. The students in the traditional classrooms favoured the training of other professionals skills, too, like problem-solving skills. However, students who studied exclusively online attributed a significantly greater overall usefulness of SWMG workshops for professional practice, compared to their peers who participated in the face-to-face laboratories. A remarkable result was that more therapeutic and support groups were preferred in the online environment, maybe related to the concerns generated by the pandemic. Remote education forced the majority of students to return to their original places of residence, mostly in the countryside, and also brought negative psychological effects caused by social isolation due to the pandemic. Remote learning is not the most desirable educational option. Students gain most from blended teaching-learning vehicles: face-to-face and online medium.